Automatic measurement of anthropometric variables for the evaluation of respiration using artificial visión - Marino-Vera, Héctor; Mendoza, Luis Enrique; Gualdrón-Guerrero, Oscar Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The speech-language evaluation of breathing is a tool important for the health professional because it allows to know the difficulties of people when breathing. This protocol is used manually with the help of a few markers, and not allows characterization of body posture, measuring to distances, angles and positions. This article presents a novel alternative in the development of a system for automatic measurements of anthropometric variables, which intervene in the phonoaudiological assessment of respiration, using artificial vision. Variables were taken on the 4 planes: frontal, posterior, left sagittal and right sagittal; Also, 32 markers were included to obtain 35 anthropometric variables. The operating principle of the automatic algorithm for the recognition of anthropometric variables was tested with two patients, achieving an overall system error rate of 2.81%. It is important to emphasize that this development will allow the specialist to rely on a digital tool to achieve more precise measurements, improving accuracy in measurements and diagnosis.